Budget advisor personal financial management software / Mutahir Mohamed Ariff - Mutahir, Mohamed Ariff (2003)
The Budget Advisor software is a stand-alone application for use on personal computers to manage one's own family finances. The management aspect that it covers is helping the user to set up the financial targets they would like to achieve in life, estimating on how to go about in realizing it and track the daily spending's so that user would stick to it. All of the information collected from the process above will be compiled and summarized so that the user can view it through easy to understand reports and graphs. In line with this, advice will also be generated to help the user along the way of better financial management. The Waterfall Model with Prototyping approach was chosen as the project development methodology because the strengths of both the Waterfall Model and prototyping can be combined in a single project and reduces the risks involved. The development tool is that of the Rapid Application Development (RAO) type which is Microsoft Visual Basic 6.0 backed by Microsoft Access as the database management system. The Budget Advisor will be developed to sport a hybrid Windows/Web interface that is easy to navigate through, just like a web browser. The report you are reading here is the final report submitted for the Budget Advisor project, developed during the course of "Projek Ilmiah Tahap Akhir I" and "Projek llmiah Tahap Akhir II". It shall give an introduction about the project, accompanied together with a literature review on materials researched and also cover the methodology used, system analysis, system design, the process I went about in system implementation and testing, the evaluation, final conclusion and finally the user manual for the Budget Advisor.